PENGARUH DIAMETER STEEL BALL SHOT PEENING TERHADAP KEKASARAN PERMUKAAN, WETTABILITY DAN LAJU KOROSI PADA STAINLESS STEEL AISI 304 - Sunardi, Sunardi; Nugroho, Aris Widyo; Julianto, Achmad Zamhari (JMPM : Jurnal Material Dan Proses Manufaktur, 2017)
Stainless steel (SS) 304 is material commonly used in biomedical applications, because this material is corrosion resistant, easyly obtained, relatively light, easyly formed and low price. However, its corrosion rate tend to be higher compared to the biomedical materials. Thus, it needs surface treatment to overcome its weakness. The purpose of this research is to determine the effect of shot peening on surface roughness, wettability and corrosion rate in Synthetic Body Fluid (SBF) of SS-304 material. The samples are circular shapes of 14 mm diameter and 4 mm thickness of SS-304 materials. The shot peening was conducted with nozzle distance of 100 mm, spraying pressure of 6 bar, spraying time of 10 minutes, and and shooting angle of 90º. Steel ball diameter being used are 0.4 mm, 0.6 mm, 0.7 mm, and the properties being characterized are surface rougness, wettability and corrosion resistance. The results shows that the shot peening can increase the surface roughness from 0.868 μm ± 0.056 μm for the raw material up to 2.248 μm ± 0.481 μm for shoot-peenned material using steel ball diameter of 0.7 mm. The corrosion resistance decreases from 55.83 ± 2.44 mpy for the raw material to 113.15 ± 7.51 mpy for the shoot-peenned material using steel ball diameter of 0.4 mm, and the increase surface hardness was found being 276 %, . In addition, wettability test indicates that sample surface after being shot peenned treatment to be hydrophilic.